La violence dans la communauté militaire - Harrison, Deborah (Criminologie, 1997)
This paper applies a broad definition of violence to the physically and economically vulnerable situation of Canadian military wives. Its reports some of the results of an institutional ethnography of Canadian military wives ' work which was carried out during the early 1990s, and which made some important discoveries about how the military's priorities and forms of organization structure the way the military treats wives, tries to control wives, and benefits from wives' unpaid work. The military's major priority, combat readiness, necessitates the control the military exercises over its members and the specific mechanism of military control known as combat unit bonding. Combat bonding is in turn characterized by cultural homogeneity and its corollaries of sexism, racism, derogation of, and violence against women. Nevertheless, the military extends a diluted form of combat bonding to military wives, in order to exert control over them and appropriate their unpaid labour, loyalty — and frequently, silence. Combat-related obsession with unit morale also often translates into the cover-up of problems, which is a consideration that adds to the isolation of the many survivors of woman abuse who are members of the military community. The greater public accountability of the Canadian military which may result from the Somalia Inquiry makes this an especially opportune time to study woman abuse and other forms of family violence in the Canadian military community.